The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1055/s-0035-1547304
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Results of Epiphyseal Transplant in Distal Radius Reconstruction in Children

Abstract: ▼Background: Replacement of osseous defect, restoration of joint function, and restoration of longitudinal growth are the 3 main reconstructive issues that need to be addressed when the physis and epiphysis are damaged in a skeletally immature individual. Failure in achieving these objectives leads to severe deformity and functional impairment, which significantly compromises the quality of life of young patients. Because of its biological and morphological characteristics, the proximal fibula epiphyseal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 21 publications
(32 reference statements)
0
22
0
1
Order By: Relevance
“…Free vascularized fibula flaps are widely used for many reconstructive scenarios, including physeal transfer first described by Innocenti et al 20 They are beneficial compared with other vascularized grafts because of the presence of an articular surface for creation of a neoarticular joint and a tubular structure for reconstruction of long bone defects. 6 , 18 , 21 In the proximal humerus, survival of the physis and creation of a neoglenofibular joint have been successful, but a high rate of graft fracture is noted, usually within the first year before enough graft hypertrophy has occurred because of the diameter mismatch between the fibula and humerus. 1 , 5 - 7 One study looked at 11 proximal humerus physeal transfers and reported a 66% graft fracture rate within the first year.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Free vascularized fibula flaps are widely used for many reconstructive scenarios, including physeal transfer first described by Innocenti et al 20 They are beneficial compared with other vascularized grafts because of the presence of an articular surface for creation of a neoarticular joint and a tubular structure for reconstruction of long bone defects. 6 , 18 , 21 In the proximal humerus, survival of the physis and creation of a neoglenofibular joint have been successful, but a high rate of graft fracture is noted, usually within the first year before enough graft hypertrophy has occurred because of the diameter mismatch between the fibula and humerus. 1 , 5 - 7 One study looked at 11 proximal humerus physeal transfers and reported a 66% graft fracture rate within the first year.…”
Section: Discussionmentioning
confidence: 99%
“…A transient peroneal palsy and foot drop is to be expected as branches of the deep peroneal nerve may need to be divided and repaired to disarticulate the fibular head during harvesting. 15 , 21 Rarely is the foot drop permanent (2.6%). 21 At the follow-up, the patient's range of motion was limited but as expected.…”
Section: Discussionmentioning
confidence: 99%
“…The palsies have been mostly transient, but some have been followed by a long-term peroneal weakness. Importantly, the potential for growth at the proximal fibula epiphysis has been questioned and may depend upon which arterial pedicle(s) is used, although recent experiences with a reversed anterior tibial artery pedicle, when replacing the distal radius in the treatment of bone malignancies, have shown a positive growth potential (Innocenti et al., 2015). Finally, we do not know if a proximal fibular epiphyseal transfer will enhance the longitudinal growth of the ulna and result in longer forearms.…”
Section: Discussionmentioning
confidence: 99%
“…Later series have cited these equivocal results to assert that the anterior tibial pedicle is the best choice to provide blood supply both to the epiphysis and diaphysis with a single pedicle. Innocenti et al 8,9 showed favourable outcomes in six children using fibular epiphyseal transfer based on the anterior tibial artery. All achieved bony union and longitudinal growth.…”
Section: Discussionmentioning
confidence: 99%